Analysis of Effectiveness for Internal Control and Supply Chain Integration Systems Implementation of Financial Fields - Yuesti, Anik; Dwi Ratnadi, Ni Made; Paulus Tahu, Gregorious (ExcelingTech, 2020)
Abstract- The purpose of this study is to analyze the effectiveness of the implementation of the Internal Control System and Supply Chain Integration in Sfinancial fields. This research method uses a type of critical qualitative research that is describing, describing, describing, assessing a condition, evaluating, and providing recommendations to SPI with observation, interviews, questionnaires, and document studies. The results of this study are the application of SPI through elements of the control environment, risk assessment, running less effectively. While the elements of control, information and communication activities have proceeded very well but in the element of monitoring by SPI ISI Denpasar running in the category is quite effective. In the control environment, it has been supported by the SPI ISI Denpasar code of ethics in upholding integrity and ethical values, organizational commitment in maintaining employee competencies, and leadership attitudes that show a conducive leadership style; risk assessment, not yet having a risk identification method only limited to the methodology of completion and follow-up problems; control activities, in carrying out the activities of the quality assurance office. In increasing the effectiveness of the implementation of the internal control system and supply chain integration at the ISI Denpasar, it needs to be supported by several things including: the application of recruitment patterns and employee career development, the application of risk identification and analysis methodologies, improving communication with external parties, implementing follow-up audit procedures and attention to completeness documentation of the results of activities.